Assessing factors influencing renewable energy deployment and the role of natural resources in MENA countries - Li B.; Amin A.; Nureen N.; Saqib N.; Wang L.; Rehman M.A. (Elsevier Ltd, 2025)
Governments worldwide are deploying renewable sources as a part of an imperative agenda to overcome the detrimental impacts of climate change and environmental degradation. Although renewable energy contains several benefits, very few researchers have worked on the determinants of renewable energy deployment and the role of natural resources in the Middle East and North Africa (MENA) countries. This research contributes to the prior literature by examining the influence of financial growth, governance, environmental quality, and economic development in MENA countries from 1990 to 2020. For empirical estimation, this study employs the latest econometric approaches: cross-sectional autoregressive distributed lag (CS-ARDL), augmented mean group (AMG), and Westerlund & Edgerton's cointegration. Furthermore, the cross-sectional augmented Im-Pesaran-Shin (CIPS) and cross-sectional augmented Dickey-Fuller (CADF) panel unit root tests are employed to check the stationarity level among variables. The empirical outcome demonstrates that governance, financial growth, the interaction term between financial growth and governance, carbon emissions, and economic development significantly and directly influence renewable energy deployment in MENA countries. As a further step, robustness is checked by employing the AMG estimator. The findings from the AMG estimator verify the robustness of the study's outcomes. Thus, the empirical and robustness results make it clear that all the aforementioned variables play a significant role in renewable energy deployment in the sampled region. The policy consequences of the major efforts are laid out as well coherently and consistently. ? 2023